High versus standard magnetic resonance image resolution of the cervical spine in patients with axial spondyloarthritis. (April 2020) - Krabbe, Simon; Østergaard, Mikkel; Sørensen, Inge J; Møller, Jakob; Jensen, Bente; Madsen, Ole R; Pedersen, Susanne J
Background: Sagittal magnetic resonance (MR) images are typically obtained with the same spatial resolution along the entire spine, but cervical vertebrae are smaller and may be harder to assess. Purpose: To investigate if high-resolution (high-res) short tau inversion recovery (STIR) and T1-weighted turbo spin echo (T1W) MR imaging (MRI) sequences are superior to standard resolution for detecting inflammatory and structural lesions in the cervical spine of patients with axial spondyloarthritis. Material and Methods: Images were obtained in 36 patients. Voxel sizes at high/standard resolution were 1.99/4.33 mm 3 (STIR) and 0.89/3.71 mm 3 (T1W). High-resolution and standard-resolution images were scored by two readers according to the Canada-Denmark (CANDEN) MRI spine scoring system. Results: Higher bone marrow edema scores were obtained at high resolution versus standard resolution (mean 2.1 vs. 1.2, P  = 0.040), whereas fat lesion scores (1.8 vs. 1.5, P  = 0.27) and new bone formation scores (3.5 vs. 2.8, P  = 0.21) were similar. High-resolution MRI did not classify more patients as positive for bone marrow edema, fat, or new bone formation in the cervical spine compared to standard resolution. Using lateral radiographs as reference standard, sensitivity for detecting anterior corner syndesmophytes with both high-resolution and standard-resolution MRI was low (range 7–22%) and sensitivity for detecting ankylosis was low to moderate (20–55%), while specificity was high (≥96%). Conclusion: High-resolution MRI allowed identification of more inflammatory lesions in the cervical spine in patients with axial spondyloarthritis when compared to standard resolution, but it did not classify more patients as positive for bone marrow edema. The slightly increased sensitivity at high-resolution MRI seemed to be too modest to have any real clinical importance.